Salvation and catastrophe (Lanham, Maryland)
xiv, 424 sayfa
Keywords: “ The Greek-Turkish War of 1919–1923—also known as the Western Front of the Turkish War of Liberation and the Asia Minor Campaign—was one of the key aftershocks of the First World War. Internationally better known for its aftermath, the Compulsory Population Exchange between Greece and Turkey, the Catastrophe of Ottoman Greeks, and the foundation of the Republic of Turkey under Mustafa Kemal Atatürk, the war has never been given a holistic treatment in English, despite its long shadow over the Greek-Turkish relationship. The contributors in this volume address this gap by brining to the fore, on its centenary, aspects of the onset, conduct, and aftermath of this war. Combining insights from the study of international relations, political science, strategic studies, military history, migration studies, and social history the contributions tell the story of leaders and decisions, battles and campaigns, voluntary and involuntary migration, and the human stories of suffering and resilience. It is aspects of the story of the last gasp of the Great War in Europe, brought to its final end with Treaty of Lausanne of 1923“ --